Graphene / Fe3O4 reinforced Cu-based composite material and preparation method thereof

Through the synergistic action of graphene and Fe3O4, the co-precipitation method is used to prepare hot-press sintering of nanoparticles and copper powder, which solves the problem of insufficient performance of Cu-based materials, and improves strength, hardness, wear resistance and corrosion resistance, and maintains conductivity and thermal conductivity, suitable for industrial production.

CN119120970APending Publication Date: 2024-12-13BEIJING NORTH VEHICLE GROUP CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411287429.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing Cu-based materials have shortcomings in improving strength, hardness, wear resistance and corrosion resistance, and it is difficult to meet high performance needs.

Method used

The coordinated action of graphene and Fe3O4 was carried out to prepare Fe3O4 nanoparticles by co-precipitation method, and mixed them with graphene dispersion and copper powder. Graphene/Fe3O4-strengthened Cu-based composite material was prepared by hot pressing sintering.

Benefits of technology

It significantly enhances the strength and hardness of Cu-based materials, maintains good electrical conductivity and thermal conductivity, improves wear resistance and corrosion resistance, extends service life, and has a simple process, low cost and is easy to industrially produce.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a graphene / Fe3O4 reinforced Cu-based composite material and a preparation method thereof.The preparation method comprises the steps that graphene powder is added into an organic solution, and graphene dispersion liquid is obtained; fe3O4 nano-particles are prepared by adopting a coprecipitation method; fe3O4 nanoparticles are added into the graphene dispersion liquid, and strengthening phase composite slurry is obtained; and copper powder is added into the composite slurry, mixed powder is obtained, the mixed powder is put into a mold to be subjected to hot pressing sintering, and the graphene / Fe3O4 reinforced Cu-based composite material is obtained. According to the thermal, electrical and mechanical properties of the strengthening phase, the strength and hardness of the Cu-based material can be remarkably enhanced, and meanwhile good electrical conductivity and thermal conductivity are kept; the wear resistance and corrosion resistance of the Cu-based material are enhanced, and the service life of the Cu-based material is prolonged; the method is simple in preparation process, low in cost and easy to realize industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and specifically relates to a graphene / Fe3O4 reinforced Cu-based composite material and a preparation method thereof. Background Art

[0002] Cu-based materials are widely used in electronics, electrical, mechanical and other fields due to their good electrical conductivity, thermal conductivity and ductility. However, with the continuous development of science and technology, higher requirements are put forward for the performance of Cu-based materials, such as higher strength, hardness, wear resistance and corrosion resistance.

[0003] As a two-dimensional material with excellent mechanical, electrical and thermal properties, graphene has great potential in strengthening Cu-based materials. Fe3O4 has good magnetic and catalytic properties, and can also bring unique properties to Cu-based composites. The synergistic effect of graphene and Fe3O4 in strengthening copper-based composites is expected to obtain new materials with excellent comprehensive properties.

[0004] At present, most products made of Cu-based composite materials need to ensure good electrical conductivity, such as the conductive copper nozzle of a welding torch, which must ensure wire feeding stability and maintain good contact to achieve stable current transmission. However, good electrical conductivity often restricts the improvement of wear resistance, making the selection and preparation of Cu-based reinforcement phases more difficult. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] The present invention provides a graphene / Fe3O4 reinforced Cu-based composite material and a preparation method thereof, so as to solve the technical problem that the existing copper-based materials have insufficient performance.

[0007] (II) Technical solution

[0008] In order to solve the above technical problems, the present invention proposes a method for preparing a graphene / Fe3O4 reinforced Cu-based composite material. The preparation method comprises the following steps: adding graphene powder to an organic solution to obtain a graphene dispersion; preparing Fe3O4 nanoparticles by a coprecipitation method; adding the Fe3O4 nanoparticles to the graphene dispersion to obtain a reinforced phase composite slurry; adding copper powder to the composite slurry to obtain a mixed powder, placing the mixed powder in a mold for hot pressing and sintering, and obtaining the graphene / Fe3O4 reinforced Cu-based composite material.

[0009] Furthermore, the preparation method specifically comprises the following steps:

[0010] S1. Preparation of graphene dispersion

[0011] Adding graphene powder into an organic solution and ultrasonically treating the solution to obtain a graphene dispersion;

[0012] S2. Preparation of Fe3O4 nanoparticles

[0013] Fe3O4 nanoparticles were prepared by coprecipitation method: ferrous chloride and ferric chloride were dissolved in deionized water, and ammonia water was slowly added under nitrogen protection to adjust the pH value of the solution to 9-11, and the solution was stirred for 1-2 hours, and then magnetic separation, washing and drying were performed to obtain Fe3O4 nanoparticles;

[0014] S3. Preparation of composite slurry

[0015] The Fe3O4 nanoparticles prepared in step S2 are added to the graphene dispersion prepared in step S1, subjected to ultrasonic treatment, and then a surfactant is added and stirred to obtain a composite slurry;

[0016] S4. Preparation of copper-based composite materials

[0017] The copper powder is added to the composite slurry prepared in step S3, stirred evenly, and then vacuum dried to obtain a mixed powder. The mixed powder is placed in a mold and hot-pressed and sintered in a hot-pressing furnace to obtain a graphene / Fe3O4 reinforced Cu-based composite material.

[0018] Furthermore, in step S1, the ultrasonic treatment is performed for 2 to 4 hours, the concentration of the graphene dispersion is 0.5 to 20 g / L, and the organic solvent is 0.5 to 2 L.

[0019] Furthermore, in step S1, the organic solution is 2-dimethylformamide, ethanol or ethyl acetate.

[0020] Furthermore, in step S1, the ultrasonic frequency is 20-100 kHz, and the ultrasonic temperature is 10-50°C.

[0021] Furthermore, in step S2, after adjusting the pH value of the solution, the reaction is stirred for 1 to 2 hours.

[0022] Furthermore, in step S3, the surfactant is 2-polyvinyl pyrrolidone.

[0023] Furthermore, in step S3, ultrasonic treatment is performed for 1 to 2 hours.

[0024] Furthermore, in step S4, the hot pressing temperature of the hot pressing sintering is 700-900° C., the pressure is 20-50 MPa, and the holding time is 1-3 hours.

[0025] In addition, the present invention also provides a graphene / Fe3O4 reinforced Cu-based composite material, and the graphene / Fe3O4 reinforced Cu-based composite material is prepared by the above method.

[0026] (III) Beneficial effects

[0027] The present invention proposes a graphene / Fe3O4 reinforced Cu-based composite material and a preparation method thereof, comprising adding graphene powder to an organic solution to obtain a graphene dispersion; preparing Fe3O4 nanoparticles by a coprecipitation method; adding Fe3O4 nanoparticles to the graphene dispersion to obtain a reinforced phase composite slurry; adding copper powder to the composite slurry to obtain a mixed powder, placing the mixed powder in a mold for hot pressing and sintering to obtain a graphene / Fe3O4 reinforced Cu-based composite material. According to the thermal, electrical and mechanical properties of the reinforced phase, the present invention can significantly enhance the strength and hardness of the Cu-based material while maintaining good electrical conductivity and thermal conductivity; enhance the wear resistance and corrosion resistance of the Cu-based material and extend its service life; the method has a simple preparation process, low cost and is easy to realize industrial production. DETAILED DESCRIPTION

[0028] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with embodiments.

[0029] The present invention provides a method for preparing a graphene / Fe3O4 reinforced Cu-based composite material, which comprises the following steps:

[0030] S1. Preparation of graphene dispersion

[0031] The graphene powder is added to the organic solution and ultrasonically treated for 2 to 4 hours to obtain a graphene dispersion with a concentration of 0.5 to 20 g / L.

[0032] The organic solution selected in the preparation of the graphene dispersion is easily volatile when heated, ensuring that the residual organic solution, such as 2-dimethylformamide, ethanol or ethyl acetate, can be conveniently and quickly removed in the subsequent preparation process; the ultrasonic frequency is set to 20-100 kHz, and the ultrasonic temperature is 10-50° C. Ultrasonic dispersion of graphene in an organic solution can effectively reduce the agglomeration of graphene, improve its dispersion uniformity in the solution, and ensure the structural integrity of graphene.

[0033] S2. Preparation of Fe3O4 nanoparticles

[0034] Fe3O4 nanoparticles were prepared by coprecipitation method: a certain proportion of ferrous chloride and ferric chloride was dissolved in deionized water, and ammonia water was slowly added under nitrogen protection to adjust the pH value of the solution to 9-11, and the reaction was stirred for 1-2 hours, and then magnetic separation, washing and drying were performed to obtain Fe3O4 nanoparticles.

[0035] The Fe3O4 nanoparticles prepared by the coprecipitation method have the advantages of good morphology, small particle size, high magnetization intensity and coercive force, and good dispersibility, which are conducive to the subsequent combination with graphene.

[0036] S3. Preparation of composite slurry

[0037] The Fe3O4 nanoparticles prepared in step S2 are added to the graphene dispersion prepared in step S1, and ultrasonic treatment is performed for 1 to 2 hours. Then, a surfactant is added and stirred evenly to obtain a composite slurry.

[0038] When preparing the composite slurry, ultrasonic treatment is beneficial to the uniform dispersion of the reinforcing phase, and the nano-Fe3O4 particles can adhere to the graphene surface. Adding a surfactant after ultrasonic treatment can effectively prevent the reinforcing phase from re-aggregating during the static state of the composite slurry, thereby ensuring the stability of the specific structure of nano-Fe3O4 attached to graphene.

[0039] S4. Preparation of copper-based composite materials

[0040] The copper powder is added to the composite slurry prepared in step S3, stirred evenly, and then vacuum dried to obtain a mixed powder. The mixed powder is placed in a mold and hot-pressed and sintered in a hot-pressing furnace at a hot-pressing temperature of 700 to 900° C., a pressure of 20 to 50 MPa, and a holding time of 1 to 3 hours to obtain a graphene / Fe3O4 reinforced Cu-based composite material.

[0041] Adding copper powder to the composite slurry, stirring it and vacuum drying it can effectively remove the surfactant and organic solvent therein, avoid the preparation defects of the composite material, and hot-pressing and sintering the final composite powder can obtain a high-density, high-performance Cu composite material.

[0042] Example 1

[0043] S1. Add 0.5 g of graphene powder into 1 L of 2-dimethylformamide (DMF) and ultrasonically treat for 2 h to obtain a graphene dispersion with a concentration of 0.5 g / L.

[0044] S2. Dissolve 100 ml / mol ferrous chloride and 200 ml / mol ferric chloride in 500 ml deionized water. Under nitrogen protection, slowly add ammonia water, adjust the pH value of the solution to 9, stir and react for 1 hour, then perform magnetic separation, wash and dry to obtain Fe3O4 nanoparticles.

[0045] S3. Add the Fe3O4 nanoparticles prepared in step S2 to the graphene dispersion prepared in step S1, ultrasonically treat for 1 hour, then add 10g of surfactant 2-polyvinylpyrrolidone (PVP), stir evenly, and obtain a composite slurry.

[0046] S4. Add 100 g of copper powder to the composite slurry prepared in step S3, stir evenly, and then vacuum dry to obtain a mixed powder. Put the mixed powder into a mold, and perform hot pressing sintering in a hot pressing furnace at a sintering temperature of 700° C., a pressure of 20 MPa, and a holding time of 1 h to obtain a graphene / Fe3O4 reinforced Cu-based composite material.

[0047] Example 2

[0048] S1. Add 1.0 g of graphene powder into 1 L of ethanol and ultrasonically treat for 3 h to obtain a graphene dispersion with a concentration of 1.0 g / L.

[0049] S2. Dissolve 150 ml / mol ferrous chloride and 300 ml / mol ferric chloride in 500 ml deionized water. Under nitrogen protection, slowly add ammonia water, adjust the pH value of the solution to 10, stir and react for 1.5 hours, then perform magnetic separation, wash and dry to obtain Fe3O4 nanoparticles.

[0050] S3. Add the Fe3O4 nanoparticles prepared in step S2 to the graphene dispersion prepared in step S1, ultrasonically treat for 1.5 hours, then add 15g of surfactant 2-polyvinylpyrrolidone (PVP), stir evenly, and obtain a composite slurry.

[0051] S4. Add 100 g of copper powder to the composite slurry prepared in step S3, stir evenly, and then vacuum dry to obtain a mixed powder. Put the mixed powder into a mold, and perform hot pressing sintering in a hot pressing furnace at a sintering temperature of 800° C., a pressure of 30 MPa, and a holding time of 2 h to obtain a graphene / Fe3O4 reinforced Cu-based composite material.

[0052] Example 3

[0053] S1. Add 2.0 g of graphene powder to 1 L of ethyl acetate and ultrasonically treat for 4 h to obtain a graphene dispersion with a concentration of 2.0 g / L.

[0054] S2. Dissolve 200 ml / mol ferrous chloride and 400 ml / mol ferric chloride in 500 ml deionized water. Under nitrogen protection, slowly add ammonia water, adjust the pH value of the solution to 11, stir and react for 2 hours, then perform magnetic separation, wash and dry to obtain Fe3O4 nanoparticles.

[0055] S3. Add the Fe3O4 nanoparticles prepared in step S2 to the graphene dispersion prepared in step S1, ultrasonically treat for 2 hours, then add 20g of surfactant 2-polyvinylpyrrolidone (PVP), stir evenly, and obtain a composite slurry.

[0056] S4. Add 100g of copper powder to the composite slurry prepared in step S3, stir evenly, and then vacuum dry to obtain a mixed powder. Put the mixed powder into a mold, and perform hot pressing sintering in a hot pressing furnace at a sintering temperature of 900°C, a pressure of 50MPa, and a holding time of 3h to obtain a graphene / Fe3O4 reinforced Cu-based composite material.

[0057] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a graphene / Fe3O4 reinforced Cu-based composite material, characterized in that: The preparation method comprises the following steps: adding graphene powder into an organic solution to obtain a graphene dispersion; preparing Fe3O4 nanoparticles by a coprecipitation method; adding the Fe3O4 nanoparticles into the graphene dispersion to obtain a reinforced phase composite slurry; adding copper powder into the composite slurry to obtain a mixed powder, placing the mixed powder into a mold for hot pressing and sintering, and obtaining a graphene / Fe3O4 reinforced Cu-based composite material.

2. The method for preparing a graphene / Fe3O4 reinforced Cu-based composite material according to claim 1, characterized in that: The preparation method specifically comprises the following steps: S1. Preparation of graphene dispersion Adding graphene powder into an organic solution and ultrasonically treating the solution to obtain a graphene dispersion; S2. Preparation of Fe3O4 nanoparticles Fe3O4 nanoparticles were prepared by coprecipitation method: ferrous chloride and ferric chloride were dissolved in deionized water, and ammonia water was slowly added under nitrogen protection to adjust the pH value of the solution to 9-11, and the solution was stirred for 1-2 hours, and then magnetic separation, washing and drying were performed to obtain Fe3O4 nanoparticles; S3. Preparation of composite slurry The Fe3O4 nanoparticles prepared in step S2 are added to the graphene dispersion prepared in step S1, subjected to ultrasonic treatment, and then a surfactant is added and stirred to obtain a composite slurry; S4. Preparation of copper-based composite materials The copper powder is added to the composite slurry prepared in step S3, stirred evenly, and then vacuum dried to obtain a mixed powder. The mixed powder is placed in a mold and hot-pressed and sintered in a hot-pressing furnace to obtain a graphene / Fe3O4 reinforced Cu-based composite material.

3. The method for preparing a graphene / Fe3O4 reinforced Cu-based composite material according to claim 2, characterized in that: In step S1, ultrasonic treatment is performed for 2 to 4 hours, the concentration of the graphene dispersion is 0.5 to 20 g / L, and the organic solvent is 0.5 to 2 L.

4. The method for preparing a graphene / Fe3O4 reinforced Cu-based composite material according to claim 2, characterized in that: In step S1, the organic solution is 2-dimethylformamide, ethanol or ethyl acetate.

5. The method for preparing the graphene / Fe3O4 reinforced Cu-based composite material according to claim 2, characterized in that: In step S1, the ultrasonic frequency is 20-100 kHz, and the ultrasonic temperature is 10-50°C.

6. The method for preparing the graphene / Fe3O4 reinforced Cu-based composite material according to claim 2, characterized in that: In step S2, after adjusting the pH value of the solution, the reaction is stirred for 1 to 2 hours.

7. The method for preparing a graphene / Fe3O4 reinforced Cu-based composite material according to claim 2, characterized in that: In step S3, the surfactant is 2-polyvinyl pyrrolidone.

8. The method for preparing a graphene / Fe3O4 reinforced Cu-based composite material according to claim 2, characterized in that: In step S3, ultrasonic treatment is performed for 1 to 2 hours.

9. The method for preparing a graphene / Fe3O4 reinforced Cu-based composite material according to claim 2, characterized in that: In step S4, the hot pressing temperature of the hot pressing sintering is 700-900° C., the pressure is 20-50 MPa, and the holding time is 1-3 hours.

10. A graphene / Fe3O4 reinforced Cu-based composite material, characterized in that: The graphene / Fe3O4 reinforced Cu-based composite material is prepared by the method described in any one of claims 1 to 9.